Energy Efficient and Node Density Based Dual Base Station Deployment for Large Scale Wireless Sensor Network - K. S. Rajeshwari, Sumithra Devi K. A. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Wireless sensor network (WSN) one of the top-rated technologies used and integrated in majority of the other technologies. WSNs come with different categories like –Industrial WSNs, Large Scale WSN, Health Sector WSNs and many others. This paper aims to review the impact of the WSNs in the current market and try to address the base station localization issues in the large scale WSNs. The main issues in the base station positioning, is to make the network energy efficient by making the nodes transfer the data to the base station with optimal energy. The proposed algorithm aims to adopt the dual base station techniques with clustering process. Each base station will be deployed based on the density of the nodes to ensure the efficient energy transfer by the sensor nodes. The proposed algorithm has proved to be efficient in terms of network lifetime.